2022
DOI: 10.3389/fmolb.2022.862932
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Erianin: Cancer-Specific Target Prediction Based on Network Pharmacology

Abstract: Erianin is a major bisbenzyl compound extracted from Dendrobium chrysotoxum Lindl., an important traditional Chinese herb. In recent years, a growing body of evidence has proved the potential therapeutic effects of erianin on various cancers, including hepatoma, melanoma, non-small-cell lung carcinoma, myelogenous leukemia, breast cancer, and osteosarcoma. Especially, the pharmacological activities of erianin, such as antioxidant and anticancer activity, have been frequently demonstrated by plenty of studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Hence, STAT-3 overexpression is thought to be a crucial target for the identi cation of new therapeutical molecules against esophageal cancer. Erianin belongs to A dibenzyl drug extracted from Dendrobium o cinale and Dendrobium chrysotoxum, commonly used in traditional Chinese medicine [17]. In this investigation, we elucidated the capacity of erianin to enhance cellular toxicity in esophageal carcinoma cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, STAT-3 overexpression is thought to be a crucial target for the identi cation of new therapeutical molecules against esophageal cancer. Erianin belongs to A dibenzyl drug extracted from Dendrobium o cinale and Dendrobium chrysotoxum, commonly used in traditional Chinese medicine [17]. In this investigation, we elucidated the capacity of erianin to enhance cellular toxicity in esophageal carcinoma cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 96%
“…Erianin is a bis benzyl compound derived from the herb Dendrohium chrysotoxum Lindl and has been used in Chinese traditional medicine as an antipyretic and analgesic [17]. Erianin possesses several pharmacological roles such as antioxidant, antiviral, improving diabetic nephropathy, antibacterial, relaxing bronchial smooth muscle, and anti-tumor [18].…”
Section: Introductionmentioning
confidence: 99%
“…This underscores the versatility and applicability of SwissTargetPrediction in elucidating the molecular targets of bioactive compounds originating from natural sources. For example, in a study of 2022, a team of researchers from China led by Lili Yan [ 33 ] examined information on the predicted molecular targets of Erianin, a biphenyl compound, using this site. They proceeded to compare the identified targets, along with results from other bioinformatic tools, with the then-current information published by other authors.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Furthermore, a network pharmacology targets prediction indicated BRAF as a potential target of erianin, in which the MAPK cascade pathway was also enriched. 22 However, the direct molecular target and correlated signaling pathway for erianin are yet to be identified. In this study, erianin was found as a CRAF and MEK1/2 dual-target inhibitor through the aid of Kinase Profiler™ enzyme profiling assay and its inhibition of disordered MAPK signaling pathway in either BRAF V600E or RAS mutant tumors.…”
Section: Introductionmentioning
confidence: 99%